Innovatives Bodeneigentum für innovative Bodenpolitik: Vier normative Grundsätze - Davy, Benjamin (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
Innovative land policy does not yield to the pressure of short-term capital exploitation. Rather, innovative land policy establishes a fair balance between the interests of landowners and the public interest. As a keystone of land policy, property – particularly if open to innovation – plays a vital role in achieving this balance. This commentary explains four normative principles that help design innovative property. Since the four principles derive from long-standing ideas about property in land, the commentary uses a distinctly conservative approach. This approach, however, is quite innovative in the face of the reductionist view of property as a right that only serves the purposes of its owners. According to the first principle, innovative land policy must pay attention to the nexus between private and common property. Under the second principle, property in land must account for the government’s positive duty to provide for adequate land uses for all. The third principle distinguishes between property rights of natural and legal persons: personal property guarantees individual liberty, but corporate property is a social function, not a right at all. The fourth principle reminds of the inseparable bond between property in land and land ethics.
Keywords: Land ethics; Land policy; Property; Social function; Individual rights